Abstracts of the 2024 Canadian Association of Medical Oncologists Annual Scientific Meeting - Alexi Campbell; Sharlene Gill; Desirée Hao; Suneil Khanna; Erin Powell; Moira Rushton; Maryam Soleimani; Stephen Welch (Current Oncology)
On behalf of the Canadian Association of Medical Oncologists, we are pleased to present the abstracts of the 2024 Annual Scientific Meeting. The CAMO Annual Scientific Meeting (ASM) took place from 24–26 October 2024 in an in-person event in Ottawa, ON. Twenty-four (24) abstracts were selected for presentation as oral presentations and poster presentations. Awards for the top three (3) abstracts were presented during the ASM; they have been marked as “Award Recipient”. We congratulate all presenters on their research work and contribution.